Experimental investigation of the effect of machinability on surface quality and vibration in hard turning of hardened AISI 4140 steels using ceramic cutting tools. (October 2021) - Kam, Menderes; Şeremet, Musa
In industry, hardened steels are used in manufacturing of the products such as machine parts and components. In this context, surface quality and vibration play a significant role for control of cutting parameters and cutting conditions in turning process of hardened steel materials. In this study, it was aimed to investigate the effect of machinability on surface quality (Ra and Rz) and vibration in hard turning of conventional heat treated (CHT) and tempered (T) AISI 4140 (42CrMo4) steel samples using ceramic cutting tools under dry environment. They were selected as cutting parameters; four different cutting speeds (120, 160, 200, and 240 m/min), three different feed rates (0.05, 0.10, and 0.15 mm/rev), and depth of cut (0.2 mm). To make the turning process more efficient and to measure the occurring vibrations, the data were obtained online from the ceramic cutting tool by accelerometers in three axes (x-Ch1, y-Ch2, and z-Ch3 directions). In addition, test results of hardness, tensile, microstructure images, Ra - Rz values, and chip thickness values of the experiment samples were analyzed and compared. With the microstructure obtained after the tempering process applied to the T sample, it was seen that it is more machinable and affects the surface quality - vibration positively. The results showed that the most important cutting parameter affecting vibration and surface quality was found to be the feed rate. The lowest Ra value was found as 0.144 μm at 200 m/min of cutting speed and 0.05 mm/rev of feed rate in the T sample. The lowest vibration amplitude value (Ch3) was measured as 0.0023 gRMS (Root Mean Square) at 120 m/min of cutting speed and 0.05 mm/rev of feed rate. According to the Ra and Rz values found in the literature studies, better surface qualities were obtained in the present study.